PENGARUH FINANCIAL DISTRESS, PERGANTIAN MANAJEMEN, UKURAN KAP DAN AUDIT FEE TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR - Maria Entina Puspita; Tika Uswatun Chasanah; Fudji Sri Mar'ati (E-Jurnal Akuntansi TSM, 2026)
This study aims to analyze the effect of financial distress, management turnover, audit firm size and audit fees on auditor switching in manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2023 period. Auditor switching is a condition where a company changes its Public Accounting Firm (KAP) or Public Accountant, so it is important to identify the influencing factors. The method used quantitative with multiple linear regression approach. Secondary data were obtained from the annual financial reports of manufacturing companies that purposive sampling criteria with sample 18 manufacturing companies. The analysis technique used the classical assumption test, multiple linear regression, t-test, f-test and coefficient of determination. The results reveal that financial distress, management turnover and audit firm size no significantly influence auditor switching, while audit fees significantly influence auditor switching. Simultaneous testing also shows that financial distress, management turnover, audit firm size and audit fees simultaneously do not significantly influence auditor switching. The coefficient determination results indicate that 7.3% of the variables contributing to auditor switching are financial distress, management turnover, audit firm size and audit fees. Other variables not yet examined in this study, such as audit delay, audit tenure and firm size contribute to the remainder. Auditor switching reflects the dynamics of the relationship between management and auditors. Therefore, investors should consider financial distress, management turnover, audit firm size and audit fees when making decisions.